No common denominator: Plant-based diets and treatment-induced neuropathy of diabetes. (August 2019) - Storz, Maximilian Andreas
Abstract: Treatment-induced neuropathy of diabetes is a poorly understood and underestimated iatrogenic complication of aggressive glycemic control in individuals suffering from diabetes. Symptoms, including severe neuropathic pain and autonomic dysfunction, usually follow an abrupt improvement in glycemic control. The latter is usually triggered by pharmacotherapy, however, treatment-induced neuropathy of diabetes (TIND) has also been associated with severe dietary restriction. Dietary modifications are of paramount importance in the treatment of type 2 diabetes. Hereby, calorie restriction and fasting diets as well as plant-based diets enjoy uninterrupted popularity. While cases of TIND have been reported with (very) low calorie diets, a case of TIND in the context of a whole-food plant-based diet has not been published to the best of my knowledge. Is this a simple coincidence or is there potentially a reason behind it? The hypothesis presented in this paper is that whole-food plant-based diets and TIND do not share a common denominator. Both evidence in support and evidence against this, admittedly, speculative hypothesis, is presented in this manuscript. A special focus is put on HbA1c dynamics with plant-based diets and reduced medication needs.